The Importance Of Communication, Leader Member Exchange (LMX), Work Environment On Job Satisfaction Of State Civil Apparatus Purwakarta District, Cilegon City - Deni Sumantri (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This research aims to find out whether communication, Leader Member Exchange, and Work Environment influence job satisfaction of the State Civil Apparatus in Purwakarta District, Cilegon City. This research was conducted using quantitative research methods. The sample selection technique taken was the Slovin method with an error rate of 10%. Respondents came from Purwakarta District, Cilegon City with a total of 62 respondents. Data was collected using a questionnaire distributed directly to respondents, and analyzed using SPSS version 25. The statistical methods used were normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis test, coefficient of determination test. The research results show that there is a significant influence between communication, Leader Member Exchange (LMX), work environment on job satisfaction partially, and there is a significant influence on communication, leader members exchange and work environment simultaneously on job satisfaction. The limitations of this research are also influenced by factors from other variables outside the research model such as compensation and work life balance, work motivation and others. It is hoped that future research will discuss beyond these variables and different locations.